2020
DOI: 10.1002/slct.202000842
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Oxyacetylacetonate Grated on Metal Organic Framework as Catalyst for the Direct Hydroxylation of Benzene to Phenol

Abstract: A high-performance NH 2 -MIL-88B(Fe)-SAÀ V for the direct catalytic oxidation of benzene hydroxylation using hydrogen peroxide as the oxidant was designed and prepared. The synthesized material was characterized by scanning electron microscopy, x-ray powder diffraction, flourier transform infrared spectroscopy and nitrogen adsorption-desorption. The influence of different parameters on the catalytic performance of NH 2 -MIL-88B(Fe)-SAÀ V for benzene hydroxylation was re-searched. Under optimized condition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The stability tests revealed that the NH 2 -MIL-88B(Fe) catalysts have good stability in water; however, their activity decreased after recycling in acetic acid, which is a solvent commonly employed in oxidation reactions. 123 Benzene hydroxylation to phenol via photocatalysis has also attracted significant attention in recent years. In most of the current reports, H 2 O 2 is employed as the oxidant and the generation of OH species has been frequently proposed as the active reactive oxygen species responsible for aromatic C-H activation.…”
Section: Nucleophilic Addition Of Benzimidazole To the Cation Can Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…The stability tests revealed that the NH 2 -MIL-88B(Fe) catalysts have good stability in water; however, their activity decreased after recycling in acetic acid, which is a solvent commonly employed in oxidation reactions. 123 Benzene hydroxylation to phenol via photocatalysis has also attracted significant attention in recent years. In most of the current reports, H 2 O 2 is employed as the oxidant and the generation of OH species has been frequently proposed as the active reactive oxygen species responsible for aromatic C-H activation.…”
Section: Nucleophilic Addition Of Benzimidazole To the Cation Can Pro...mentioning
confidence: 99%
“…The stability tests revealed that the NH 2 -MIL-88B(Fe) catalysts have good stability in water; however, their activity decreased after recycling in acetic acid, which is a solvent commonly employed in oxidation reactions. 123…”
Section: Mechanism and Behavior Of Porous Materials As Catalysts For ...mentioning
confidence: 99%
“…In 2020, Zhang and coworkers anchored vanadium oxyacetylacetonate [VO(acac) 2 ], a typical homogeneous catalyst showing high activity for benzene hydroxylation, on another amino-functionalized Fe-MOF, NH 2 -MIL-88B(Fe). 182 The heterogenization of homogeneous catalysts is beneficial for recovering the catalyst and purifying the product, which are crucial in industrial application. With the help of H 2 O 2 as the oxidant, the yield and selectivity for phenol by NH 2 -MIL-88B(Fe)-SA-V were as high as 22.2% and 98.6%, respectively, under visible light irradiation for 4 h. It should be noted that considering the good performances of Fe-MOFs as Fenton-like catalysts because of their iron-oxo clusters, most Fe-MOF photocatalysts for organic reactions need to consume additional H 2 O 2 as the oxidant to produce ˙OH reactive species, which seems less favorable for industry compared to O 2 or air.…”
Section: Mof-based Catalystsmentioning
confidence: 99%
“…The excellent catalytic performance of UiO-66-NH 2 -SA-V was attributed to the vanadium species, with high catalytic activity, and the interaction between the Zr-MOF support and benzene molecules. In a later work [ 86 ], the UiO-66-NH 2 was replaced with NH 2 -MIL-88B(Fe) to prepare a high-performance catalyst NH 2 -MIL-88B(Fe)-SA-V, which could effectively promote the adsorption of benzene on the catalyst to generate phenol and further improve the yield of phenol to 22.2%.…”
Section: Heterogeneous Photocatalysts For Hydroxylation Of Benzene To...mentioning
confidence: 99%